2018
DOI: 10.1002/ar.24012
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and NUCB2/Nesfatin‐1 Co‐Localization With Digestive Enzymes in the Intestine of Pejerrey (Odontesthes bonariensis)

Abstract: Ghrelin (orexigenic) and nesfatin‐1 (anorexigenic) are two peptides with opposing actions on food intake regulation and are mainly expressed in the hypothalamus and gut of mammals and fish. Both are involved in the regulation of a wide range of physiological processes in vertebrates, including metabolism, growth, and reproduction. However, the anatomical relationship between these peptides and the nutrient assimilation processes are not well understood. Thus, the aim of this work was to determine the localizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Data are the mean ± activity was found in early and late pre-juveniles. This suggests that this activity could correspond to a sucrase-independent maltaseglucoamylase complex (Bertucci et al, 2019;Brun et al, 2020;Chaudet et al, 2019;Dhital et al, 2013;Morelos-Castro et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Data are the mean ± activity was found in early and late pre-juveniles. This suggests that this activity could correspond to a sucrase-independent maltaseglucoamylase complex (Bertucci et al, 2019;Brun et al, 2020;Chaudet et al, 2019;Dhital et al, 2013;Morelos-Castro et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Nesfatin-1, a neuronal peptide responsible for regulating food intake and inducing satiety, is expressed in the hypothalamus and central nervous system (Goebel et al 2009 ; Goebel-Stengel et al 2011 ). However, recent studies revealed that NUCB2/nesfatin-1 is not only expressed in the hypothalamus, but also peripheral organs such as the pancreas, stomach, intestines, liver, kidneys, and adipose and reproductive tissues (Schalla and Stengel 2018 ; Bertucci et al 2019 ; Puzio et al 2021 ; Goyal and Dhar 2022 ). We have also demonstrated the expression of NUCB2/nesfatin-1 in the reproductive organs of mice, including ovaries, the uterus, and testes (Kim et al 2011 ; Kim et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports demonstrated that nesfatin-1 is also expressed in peripheral organs of humans and rodents, and functions as a regulatory peptide (Dore et al 2017 ). In rats, nesfatin-1 immunoreactivity has been identified in the gastric tract, suggesting that it has a role in gastrointestinal function (Li et al 2013 ; Bertucci et al 2019 ). Nesfatin-1 is expressed in ghrelin-secreting X/A-like cells in the stomach, which stimulate appetite (Stengel et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nesf-1 ir-cells were found in the feeding regulatory nuclei of the hypothalamus and anterior intestine of the goldfish [14] and in the mucosal cellular layer of the anterior gastrointestinal tract in zebrafish [16]. NUCB2/Nesf-1 and ghrelin co-localize in the enteroendocrine cells of the anterior intestine [17] and in the hepatopancreas of goldfish [18], in the gut mucosal cells of zebrafish [16], and in intestinal enteroendocrine cells of pejerry [19]. Furthermore, the anorexigenic role of Nesf-1 seems to also be conserved in goldfish and Ya-fish, where central or peripheral administration of Nesf-1 induces feeding behavior suppression [14,15,17] as well as in Siberian sturgeon, where it acts through the cholecystokinin signal pathway [20,21].…”
Section: Introductionmentioning
confidence: 97%